Irreversible cardiotoxicity induced by trastuzumab: a systematic review based on a pharmacovigilance case report - Lechuga-Noa, Víctor E. (2025)
Irreversible cardiotoxicity (IC) induced by trastuzumab (TZB) is a rare but serious adverse event. As a result, its characteristics and the specific factors related to exposure remain poorly understood. This study aims to synthesize and evaluate the existing evidence on IC. We presented a pharmacovigilance case of longterm IC and conducted a systematic review (SR) of the clinical manifestations of cases reported worldwide. We reported the case using the CARE guidelines checklist and assessed the causality using the modified Algorithm of Karch and Lasagna. Following PRISMA guidelines, we conducted the SR using defined terms in PubMed, Embase, Scopus, and Web of Science from inception until June 2023. This SR included five case reports, including the pharmacovigilance case reported by us. While patients exhibited different severe clinical characteristics, receiving TZB at a 6 mg/kg dose was consistent. Despite varying treatment durations, the median time of IC diagnosis was 10 months, and the average difference between the basal and the final left ventricular ejection fraction was roughly 30%. According to the modified Karch and Lasagna algorithm, all cases were ranged from possible to probable. While TZB is generally considered a reversible cardiotoxic antineoplastic, clinicians and regulators must be aware of the potential IC risk with long-term manifestations. Vigilant cardiac monitoring and further research are crucial to better understanding and managing this serious adverse event.